"Give Me Aladdin's Lamp”: A Possible Perspective of Modernism - Ştefan, Angi (Musicology Papers, 2011)
Defining the differentiated semantics of new and novelty, reversing the dictum non nova sed nove into non nove sed nova, the author of the chamber cantata „Give me Aladdin’s lamp” is based on the rich experience of leading myriad of mid-century modernism. The investigation of the paradigms of new relationships between vocal and instrumental in creation of Dora Cojocaru, is directed in present at the chamber cantata for mezzo-soprano, brass quintet and percussion on lyrics by Emil & Dan Botta, Georg Trakl, Rainer Maria Rilke and Ady Endre (1998). The relations text - melody by their phenomenological reduction to fruitful combinations between poetic word - musical sound in Dora Cojocaru’s cantatas represent a stylistic-rhetorical subsumption of autochthonous and foreign experiences in promoting new compositional and interpretive skills meant for adaptation of appropriate musical expression in portraying contemporary aesthetic message. They are designed on the wide range of contemporary aesthetic values from the grotesque in nascendi to the absurd in morendi. As long as the Cantata Galgenlieder in der Nacht with lyrics by Christian Morgenstern (1995) is conceived at the grotesquely pole on the axis of the field of contemporary aesthetics, the Cantata Give me Aladdin’s lamp is designed in the sphere of the tragic. In the composer’s vocal and instrumental creation (and not only in them) the experiences of today’s musical composition and interpretation are rethought creatively, suggesting in perspective the permanence of modern horizons.